ANALISIS PERBANDINGAN EFISIENSI PERBANKAN SYARIAH DAN KONVENSIONAL DI INDONESIA - Rio Novandra (Jurnal Ekonomi dan Pembangunan, 2025)
Global crisis give big impact to entire banks performance all over the world include banks in Indonesia. Since 1992 Indonesias banking use dual banking system, conventional and sharia banking. This research use non- parametric approach, DEA (Data Envelopment Analysis), to compare the efficiency level between conventional and sharia banking in Indonesia’s banking industry. This reseacrh did not use any sampling methods but used all of conventional and sharia bank in Indonesia, and also used period data 2008-2013. Then for see how much the differences between conventional and sharia efficiency, this research use paired t-test. These findings show the empirical evidence that sharia banking can reduce the effect of global financial crisis.